Correlation of Triethylamine N-oxide (TMAO), LPS, and TNF-Alpha Levels With Clinical Features of the Disease in Patients With and Without Septic Shock Infected With COVID-19 Virus - Polat, Kubra; Gomleksiz, Mehtap; Oral, Kubra; Gozel, Nevzat; Solowski, Gawe; Kaymaz, Tugce; Gursu, Mehmet Ferit (Elsevier, 2024)
Background: Inflammation is a response of the immune system to protect the body against various diseases or injuries. Serum trimethylamine N-oxide (TMAO) levels may vary depending on age, gender, habits, comorbidities, and microbiota. Aims: In this study, we investigated whether TMAO levels have diagnostic significance and their potential as a marker in the early diagnosis of the disease. Another aim of the research was to identify changes in TMAO levels as a reflection of the deterioration in the microflora, and IL-6, IL-10, IL-1 beta, TNF-alpha, and LPS levels in patient groups. Then, we recognized relationships between these parameters in patients infected with COVID-19 without septic shock and with COVID-19 who were without transmission of COVID-19 in septic shock. Study design: A total of 160 patients were investigated, including 40 patients infected with COVID-19 without septic contact, 40 patients with COVID-19 positive septic shock, 40 patients with COVID-19 negative septic shock, and 40 healthy individuals as the control group. Results: TNF-alpha and IL-1 beta levels were significantly lower (P < 0.001) and IL-6 and IL-10 levels were significantly higher (P < 0.001) in patient groups than in control groups. IL-1 beta showed a significant decrease, especially in the groups infected with COVID-19. Although IL-6, increased even more in the groups infected with COVID-19. Conclusions: LPS level was remarkably high in the sepsis group infected with COVID-19 compared to the other groups. TMAO level was significantly higher (P < 0.001) in the sepsis group. Therefore, TMAO is a potential biomarker in sepsis and septic shock.
Keywords: COVID-19; SARS-CoV-2; Sepsis; Septic shock; TMAO